Say, you have an expression which looks like this:
myexpr = (mess)+(some other mess)/( (mess)^3+(some other mess)^2 )^(1/3)
Here the 'mess' in the name of terms stands for what it is - a mess. To make it look nicer I use replacement rules and substitute (mess)->u, (some other mess)->v as follows
myexpr /. {(mess)->u,(some other mess)->v}
so that the output would look as nice as
u+v/(u^3+v^2)^(1/3)
Now, I actually don't get this result because when done as above the rules are not applied inside the cubic root, so the output I get instead is
u+v/( (mess)^3+(some other mess)^2 )^(1/3)
The question is, naturally, how can the full replacement be achieved with minimum pain? Thanks.
ReplaceRepeated
$\endgroup$